Ethylcellulose as a coating material in controlled-release fertilizers - Lubkowski Krzysztof (Polish Journal of Chemical Technology, 2019)
Ethylcellulose polymer was used as a coating material in the preparation of controlled release fertilizers. The materials have been prepared with the use of an immersion method. The mass ratio of polymer to fertilizer was in the range of 0.165–0.285 and the layer thickness was in the range of 204–244 μm. Mechanical properties of the prepared materials were significantly better in comparison with the initial fertilizer. Measurements of time and the degree of release of mineral components from the obtained materials were determined with a standard method. Ethylcellulose-coated materials have met the requirements of controlled release fertilizers.